Domestic constraints on the global impact of US development transnational NGOs. Issue 6 (17th August 2020) - Mitchell, George E.; Stroup, Sarah S.
ABSTRACT: Transnational NGOs (TNGOs) confront challenging operational environments in the pursuit of their missions. Less attention is typically paid to the cultural and regulatory home environments of TNGOs that can also shape their influence and impact. As US-based TNGOs confront criticisms about their accountability, legitimacy, and effectiveness, this article critically examines the impact of the cultural and regulatory environments for US-registered TNGOs. Because of the prominence of US-based organisations in TNGO governance structures and in the global development sector more generally, features of the US environment can have significant repercussions for the sector as a whole.